The International Conference Noise Control 82 - ENGEL, Zbigniew (Archives of Acoustics, 1983)
The International Conference NOISE CONTROL 82 took place in Kraków on 20-22 September, 1982. It was organised by the Commitee on Acoustics of the Polish Academy of Sciences, the Polish Acoustical Society and the Institute of Mechanics and Vibroacoustics of the Academy of Mining and Metallurgy, in cooperation with the Central Institute of Occupational Safety, the Institute of Building Technology and the Institute of Fundamental Technological Research.